An efficient framework for particle-fluid interaction using Discrete Element Lattice Boltzmann Method: Coupling scheme and periodic boundary condition. (15th August 2020) - Chen, Yilin; Jin, Guangqiu; Zhang, Pei; Galindo-Torres, S.A.; Scheuermann, A.; Li, Ling
Highlights: Combination of periodic boundary and efficient searching algorithms in Discrete Element Method and Lattice Boltzmann Method. Periodic boundary for Immersed Boundary Method in Discrete Element Lattice Boltzmann model. Efficient algorithms to detect particles collision in Immersed Boundary Method. Abstract: Discrete modeling of particle-fluid interaction was of great importance for its wide applications in chemical, petroleum and geotechnical engineering. Using Immersed Boundary Method (IBM) to couple Discrete Element Method (DEM) with Lattice Boltzmann Method (LBM) was adopted by many researchers to study particle-fluid systems. However, to accurately simulate the behavior of a large number of particles in the fluid, a huge computational power wasrequired to fully resolved the motion of each particle and an intensive search of particles' contacts was needed to account for the collision between particles. In this paper, a periodic boundary was proposed for coupling DEM with LBM using IBM and an efficient particle contact detection algorithm was developed to further reduce the computation cost. The model was validated by several well-defined benchmark including: a single particle settling in a box, particle spinning in a channel and the well-known 'Drafting, Kissing and Tumbling' (DKT) effect of two settling disks. The model's applicability was exhibited in the simulation of sediments movement in a channel, which agreed well with previous experiments. These results showed the potential usage of present numerical model to investigate in particle-fluid interaction systems.